CHIONANTHUS (OLEACEAE) IN SULAWESI, INDONESIA, INCLUDING THREE NEW SPECIES - RUTH KIEW (REINWARDTIA, 2015)
KIEW, R. 2015. Chionanthus (Oleaceae) in Sulawesi, Indonesia, including three new species. Reinwardtia 14(2): 287 - 295. - The genus Chionanthus (Oleaceae) in Sulawesi is revised. Nine species are described of which C. kostermansii Kiew, C. sordidus Kiew and C. sulawesicus Kiew are new species. Four species are endemic, C. celebicus Koord., C. sordidus, C. stenurus (Merr.) Kiew and C. sulawesicus. The geographic range of C. cordulatus Koord. extends to Borneo and Mollucas, while C. kostermansii also occurs in Sumbawa and Flores, and the range of C. rupicolus (Lingelsh.) Kiew extends to Sumbawa, Mollucas, New Guinea and the Bismarck Archipelago. Chionanthus polygamus (Roxb.) Kiew and C. ramiflorus Roxb. are both widespread species, the former from Sumatra to New Guinea and the latter from continental Asia to the Solomon Islands. A key to identify the species is provided. Chionanthus gigantifolius Koord. remains incompletely known.